Dry swing training with a light bat increases bat speed - Yano, Y.; Yabe, K.; Okuno, S.; Nagao, R.; Naka, K.; Honma, K.; Yamamoto, S.; Iwata, A. (Journal of Human Sport & Exercise, 2019)
Baseball training usually includes dry swing training to improve batting ability. However, no consensus has been reached on the relationship between bat weight and the increase in post-dry swing training bat speed. We hypothesized that dry swing training with a light bat would increase post dry swing training bat speed. Therefore, the purpose of this study was to examine the effect of dry swing training with a light bat on post dry swing training bat speed by comparing a light bat group with a heavy bat group. A total of 34 healthy male students from a university baseball team were randomly divided into a light bat group (n = 17) and a heavy bat group (n = 17). Subjects performed 100 dry swings per day, twice a week for eight weeks. The light bat group performed dry swing training with a 10.6 oz bat and the heavy bat group with a 38.8 oz bat. Bat speed and muscle power were measured before and after the intervention. There was no interaction between the intervention and post dry swing training bat speed, knee extension strength, shoulder horizontal flexion, or hand grip strength. There was a main effect of the intervention on post dry swing training bat speed and shoulder horizontal flexion. Bat speed increased in both groups, but without significant group differences in intervention effects. Since light bat loads in this study were very low, dry swing training with a light bat may be more effective and less strenuous.